Palliative and End-of-Life Care in the Home in Regional/Rural Victoria, Australia: The Role and Lived Experience of Primary Carers - Elizabeth M. Miller PhD, BN, RN; Joanne E. Porter PhD, MN, Grad Dip CC, Grad Cert Ed, Grad Dip HSM, BN, RN; Rebecca Peel MEd, Grad Dip ICU, Grad Cert HPE, BN, RN (SAGE Publishing, 2021)
Introduction Palliative support services (generalist or specialist) can provide much-needed assistance to carers who are providing palliative and end-of-life care in their homes, but access to such services in regional and rural areas of Australia is poorly understood. Objectives This study aimed to explore the role and lived experience of primary carers who are providing palliative and end-of-life care in the home in regional/rural Victoria, Australia. Methods Nine female participants, of whom six were bereaved between 7 and 20 months were interviewed using a semistructured interview technique. Each interview was audio-recorded, transcribed verbatim, and analyzed thematically. Results Two themes emerged: " Negotiating healthcare systems " which described the needs for multidisciplinary supports and " The caring experience " which discussed daily tasks, relationships, mental and physical exhaustion, respite, isolation, medication management, and grief and loss. Findings show that regional/rural carers have an added burden of travel stress as well as feeling overwhelmed, isolated, and physically and emotionally exhausted. Carers would benefit from greater flexibility for short-term respite care. The engagement of specialist palliative care services assisted the participants to navigate the health care system. Some participants did not understand the value of palliative care, highlighting the need for general practitioners to conduct early conversations about this with their patients. Education is needed to build capacity within the primary palliative care workforce, confirming the importance of timely referrals to a specialist palliative care practitioner if pain or symptom control is not effectively managed. Conclusion Providing palliative and end-of-life care in the home is an exhausting and emotionally draining role for unpaid, primary carers. Multiple supports are needed to sustain primary carers, as they play an essential role in the primary health care system.